Analysis of the Effect of Aggregate Gradation Size (0.2 – 2cm) on the Compressive Strength of Porous Concrete for Parking Applications - Dilla Natasya Amelia; Dedy Rutama; Lintang Dian Artanti (Journal of Global Engineering Research and Science, 2025)
Many parking lots are not well designed, so they often experience waterlogging due to rain, which disrupts user comfort and causes damage to infrastructure. Porous concrete is one of the new innovations being developed. This study uses various aggregate gradations to evaluate the mechanical characteristics and physical properties of porous concrete with a design compressive strength of K-150 kg/cm2. This study aims to analyze the effect of aggregate gradation with a size of 0.2 cm to 1.2 cm on the compressive strength and porosity of porous concrete used in parking lot applications. The research method applies an experimental approach in the laboratory, with compressive strength testing referring to ASTM C39 and concrete porosity referring to ASTM C192-2012. The results show that aggregate gradation of 0.2 cm - 0.7 cm has a greater average compressive strength at the age of 28 days, namely 90.19 kg/cm2 but the porosity value is smaller, namely 24.29%. Aggregates with an aggregate gradation of 0.7 cm - 1.2 cm showed an average compressive strength value of 85.06 kg/cm2 and a porosity value of 28.7% while aggregate gradations with a size of 1cm - 2 cm showed a small average compressive strength value at the age of 28 days of 80.01 kg/cm2 but the porosity value obtained was higher at 30.5%. In this test, the compressive strength at the age of 28 days with an aggregate gradation of porous concrete of 0.2 cm - 0.7 cm still meets the SNI 03-0691-2022 standard for Class B qualification (parking lot)